The Differences in Use of Connectors between British L1 Users of English and Swedish L2 Users of English - Matinlassi, Patrik (My University, 2024)
This is an MA thesis that studies how L1 English users from the UK and L2 English users from Sweden use connectors in their texts to create cohesion, as well as if there are major differences in the types of connectors used. It will use contrastive rhetoric as a framework to ground the study in. The texts come from two corpora, the British Academic Written English corpus and the Uppsala Student English corpus. Both corpora collected texts from university level students to make the texts as comparable as possible. Due to the British corpus containing a higher number of texts, the numbers were normalized by multiplying the Uppsala text count by 5.33. The texts were then put into the WordSmith software where it was possible to search for the key terms from all the texts. The results of the study did show differences between the two groups, but it is difficult to draw very strict conclusions where one group would have performed better, due to cohesion being created in many different ways and different subjects requiring different levels of explicit cohesion. In general however, the British corpus featured more varied vocabulary and their Uppsala peers did not use a single connector that was not used at least once by the British group. However, the Swedish group then used certain words more commonly than the British group. Overall in terms of semantic categories, the Swedish group used sequential connectors the most, but the British group dominated with additive, causal and adversative connectors.
Keywords: Cohesion, connector, contrastive rhetoric, corpus study, CEFR